Exploring church members' perceptions towards physical activity, fruits and vegetables consumption, and church's role in health promotion: implications for the development of church-based health interventions - Oluwakemi Odukoya; Ikenna Molobe; Oridota Olufela; Esther Oluwole; Victoria Yesufu; Folasade Ogunsola; Kolawole Okuyemi (AOSIS, 2023)
Background: The study explored the perceptions of church members towards physical activity (PA), the consumption of fruits and vegetables (FV), and the church's role in health promotion prior to the development of a church-based intervention for physical activity and fruit and vegetable consumption in Lagos, Nigeria. Method: Sixteen focus group discussions (FGD) and eleven key Informant Interviews (KII) were conducted. Eight FGDs among adults and four among the youth and the elderly church members. Key informant interviews were held among church leaders and members of the church medical advisory. Study findings were categorized under thematic headings. Based on the data analysis, several key themes were identified: the knowledge of the concept of health and common health problems, opinions of physical activity, opinions of healthy eating and fruit and vegetable consumption, types and attitudes towards existing church-based health programs and the role of the church in health promotion and church-based health programs. Within each theme, several child-themes were noted such as the challenges with fruit and vegetable consumption, biblical support for physical activity and fruit vegetable consumption, the role of the church leaders, program sustainability and barriers to participation. Results: The participants perceived health not only as the absence of disease but as general well-being of the body and soul. Health was also related to the ability to perform religious activities. Common health problems included a mix of communicable and non-communicable diseases. They are aware that physical activity, fruits and vegetables are essential for healthy living. The youth saw it as a means of improving their physical appearance however the elderly expressed concerns about the possibility of associated trips and falls. Overall, they viewed fruits and vegetables as healthy foods while processed western foods were perceived as unhealthy. Fruits and vegetables were seen as beneficial primarily to aid food digestion, boost immunity, improve youthfulness, aid weight control and to prevent chronic disease. The study participants agreed that the church, as an institution, has a significant role to play in promoting the health of her members. Instituted health committees embedded within existing church structures often lead church-based health-promoting activities and are imperative for sustainability. Types of health programs included health talks, screening programs for common NCDs, sport competitions, distributions of FV during church ceremonies such as harvests, Lenten seasons, Love feasts and church bazaars. Health outreaches were seen as a means of evangelism, and it was unanimously agreed that the Bible supports PA and healthy eating. Generally, the respondents had positive attitudes towards church-based health programs and they advised that future programs include the use of technology and should be integrated into existing church activities to improve participation. The participants also noted that the opinion of the church leaders influences the behaviours of church members and their support is critical in the development and implementation of church-based health programs. Conclusion: Church members are aware that physical activity and the consumption of fruits and vegetables are important for healthy living and expressed support for church-based health programs. They believe that the Bible supports the promotion of PA and FV consumption as healthy behaviours. Program integration, the use of technology and support of church leaders and existing church medical advisory groups are imperative for developing and sustaining church-based health programs.